Yield Performance of Sesame (Sesamum indicum L.) Varieties as Influenced by Sowing Dates and Intra-Row Spacing in the Sudan Savanna, Nigeria (Sahel Journal of Life Sciences FUDMA, 2026)
Bilocation trials were conducted in 2023 wet season to investigate the productivity of sesame varieties as influence by varieties, sowing date and intra-row spacing at the Teaching and Research Farm of Federal University Dutsin-Ma and College of Agriculture, Hassan Usman Polytechnic, Katsina. The treatments were 3 sesame varieties (EX-SUDAN, KENANA-4 and E8), 3 sowing dates (First, second and third weeks of July), and 4 intra-row spacings (10cm, 15cm, 20cm and 25cm). Using a split plot design with sowing dates and intra-row spacing as main plot treatments and variety as sub-plot treatment and replicated 3 times. EX-SUDAN was better than other varieties in term of number of capsules, number of seeds per capsule, 1000 seed weight, seed yield per plant and seed oil yield.Â  Additionally, EX-SUDAN produced more seeds per hectare in Dutsin-Ma (659.19 kg ha-1) and Katsina (596.44 kg ha-1). Second week of July had higher seed output per hectare in Dutsin-Ma (696.31 kg ha-1) and Katsina (608.31 kg ha-1) compared to the first and third weeks of July, However, seed oil and crude protein were higher during the first week of July,.There was a remarkable increase from the lower spacing of 10 cm (612.19 Kg ha-1) to the higher spacing of 25 cm (671.33 Kg ha-1), and from (504.78 Kg ha-1) to (663.56 Kg ha-1) in Dutsin-Ma and Katsina respectively. In conclusion, EX-SUDAN variety seeded in second week of July with Intra-row spacing of 25 cm is suggested at the study area for a higher yield.